(untitled) (Philological Studies, 2019)
The article focuses on selected examples of language errors made by native speakers of Russian in their spoken Slovene. All analysed examples origin in the transfer of structures from the foreign language, in our case Russian, which is also known under the term of “interference”. One of the aims is to demonstrate the repeatability of these errors by presenting their occurrence in individual speakers as well as in the group as a whole. Featured interference errors are analyzed and presented on different levels of language and are further divided into individual groups.